L'ischémie myocardique silencieuse: Ver une approche pratique - Beaudry, Philippe R. (1991)
How widespread is silent myocardial ischemia and should we be actively looking for it? If found, how should it be treated? Is the prognosis for silent myocardial ischemia different from that for symptomatic myocardial ischemia? In this article, we shall summarize what is known about this coronary disease, then present a practical approach which, hopefully, will answer these questions.